Gel electrolytes with a wide potential window for high-rate Al-ion batteries. Issue 35 (23rd August 2019) - Yu, Zhijing; Jiao, Shuqiang; Tu, Jiguo; Song, Wei-Li; Lei, Haiping; Jiao, Handong; Chen, Haosen; Fang, Daining
Abstract : A novel gel electrolyte with wide electrochemical potential window for high-rate Al ion batteries is achieved. Abstract : The electrolyte system of rechargeable aluminium-ion batteries (AIBs) is an urgent topic on account of the development in large-scale applications. In addition to the energy storage capabilities, enlargement of the electrolyte potential window is also a significant strategy for substantially boosting the energy density of the AIBs. To achieve these goals, here we demonstrate an Et3 NHCl-based gel-polymer electrolyte with a wide electrochemical potential window for high-rate quasi-solid-state AIBs. Particularly, such a quasi-solid-state AIB presents stable specific capacities, maintaining around 90 mA h g −1 with long-term cycling under a high current density. More importantly, the Et3 NHCl-based gel-polymer electrolyte here is not only favorable for increasing the cut-off charging potential, but also has various advantages, including a robust electrode–electrolyte interface, wide-temperature operating abilities and stability in a moist environment. Thus, the results may open a new avenue for low-cost and safe energy storage systems based on electrochemical technologies and applications.